Hubungan Kebugaran Jasmani dengan Prestasi Belajar pada Siswa Sekolah Menengah Atas di Semarang: The Relationship Physical Fitness with Learning Achievement of High School Students in Semarang - Nidya, Indriana Rahma; Kartini, Apoina; Suyatno, Suyatno (Amerta Nutrition, 2024)
Background: Many parents encourage their children to take additional lessons to enhance their academic performance, while other important aspects, such as students' physical fitness, are often overlooked. Objectives: This research investigates the relationship between physical fitness and learning achievement among high school students in Semarang. Methods: This observational study employed a cross-sectional design and involved 396 high school students in Semarang, with 86 subjects selected randomly. The dependent variable was learning achievement, measured by the raw scores of the final semester exams. The independent variable was physical fitness, while the other confounding variables included nutritional status, food consumption, socioeconomic conditions, health status, and participation in private tutoring. Dietary intake was assessed using a 24-hour food recall method. Body Mass Index for age (BMI/A) was calculated using weight and height to evaluate nutritional status. The multistage fitness test was utilized to assess physical fitness. Additional data were collected through interviews. Data analysis was conducted using chi-square tests and multiple logistic regression. Results: The results indicated that most subjects had inadequate nutrient intake, with low percentages for energy (55.8%), carbohydrates (76.7%), protein (45.3%), and iron (64%). In contrast, fat intake was predominantly categorized as excessive (39.5%). While most subjects exhibited good nutritional status (79.1%), their physical fitness levels were primarily poor (58.1%). Multivariate analysis revealed that good physical fitness and participation in additional lessons were positively correlated with learning achievement (p-value=0.025, p-value=0.017). Conclusions: Enhancing physical fitness is essential for improving student learning outcomes. Participating in supplementary activities, such as attending additional lessons, is also necessary to improve student learning achievement.